Targeting endothelin receptor signalling overcomes heterogeneity driven therapy failure. Issue 8 (12th June 2017) - Smith, Michael P; Rowling, Emily J; Miskolczi, Zsofia; Ferguson, Jennifer; Spoerri, Loredana; Haass, Nikolas K; Sloss, Olivia; McEntegart, Sophie; Arozarena, Imanol; von Kriegsheim, Alex; Rodriguez, Javier; Brunton, Holly; et al.
Abstract: Approaches to prolong responses to BRAF targeting drugs in melanoma patients are challenged by phenotype heterogeneity. Melanomas of a "MITF‐high" phenotype usually respond well to BRAF inhibitor therapy, but these melanomas also contain subpopulations of the de novo resistance "AXL‐high" phenotype. > 50% of melanomas progress with enriched "AXL‐high" populations, and because AXL is linked to de‐differentiation and invasiveness avoiding an "AXL‐high relapse" is desirable. We discovered that phenotype heterogeneity is supported during the response phase of BRAF inhibitor therapy due to MITF‐induced expression of endothelin 1 (EDN1). EDN1 expression is enhanced in tumours of patients on treatment and confers drug resistance through ERK re‐activation in a paracrine manner. Most importantly, EDN1 not only supports MITF‐high populations through the endothelin receptor B (EDNRB), but also AXL‐high populations through EDNRA, making it a master regulator of phenotype heterogeneity. Endothelin receptor antagonists suppress AXL‐high‐expressing cells and sensitize to BRAF inhibition, suggesting that targeting EDN1 signalling could improve BRAF inhibitor responses without selecting for AXL‐high cells. Synopsis: Melanoma heterogeneity challenges durable responses to BRAF targeting. During BRAF‐inhibitor treatment endothelin‐1 (EDN1) supports phenotype heterogeneity thereby allowing outgrowth of resistant cells. Blocking EDN1 signalling can overcome this support. Phenotype heterogeneity in melanoma is characterised by MITF‐high and AXL‐high subpopulations. Tumours enriched in AXL‐high subpopulations are resistant to BRAF‐inhibitor treatment. BRAF inhibitor‐responding tumours contain a small population of AXL‐high cells. Treatment with BRAF inhibitor induces upregulation of EDN1, and paracrine acting EDN1 supports the outgrowth of AXL‐high subpopulations. Treatment with EDN receptor (EDNR) antagonists overcomes paracrine EDN1 signalling and prolongs BRAF‐inhibitor responses. Abstract : Melanoma heterogeneity challenges durable responses to BRAF targeting. During BRAF‐inhibitor treatment endothelin‐1 (EDN1) supports phenotype heterogeneity thereby allowing outgrowth of resistant cells. Blocking EDN1 signalling can overcome this support.